Promoting Angiogenesis Effect and Molecular Mechanism of Isopropyl Caffeate (KYZ), a Novel Metabolism-Derived Candidate Drug, Based on Integrated Network Pharmacology and Transgenic Zebrafish Models - Kong, Haotian; Wang, Songsong; Zhang, Yougang; Zhang, Yangtengjiao; He, Qiuxia; Dong, Rong; Zheng, Xiaohui; Liu, Kechun; Han, Liwen (Frontiers in Pharmacology, 2022)
Aim of the study: Ischemic diseases have a huge impact on people's health, which can cause blood supply blockage or restriction in specific tissues. Researchers must develop novel drugs with great efficacy and low toxicity for the prevention and treatment of such diseases. Isopropyl caffeic acid (KYZ) was one of the metabolites of caffeic acid in vivo. This study is to explore the protective effect and mechanism of KYZ on ischemic disease from the perspective of angiogenesis in vivo and in vitro, providing support for the treatment of ischemic diseases and the discovery of a new candidate drug. Methods: The network pharmacology and molecular docking were used to predict the targets of KYZ. In addition, the effects of KYZ on damaged and normal blood vessels were evaluated using the Tg (fli1: EGFP) transgenic zebrafish. The HUVECs model was used to study the effects of KYZ on proliferation, migration, and tube formation. The same dosage of CA was also administered in vitro and in vivo at the same time to assess the pharmacodynamic difference between the two compounds. Western Blot and ELISA methods were used to detect the expression of related target proteins. Results: The result from the network pharmacology indicated that the targets of KYZ were related to angiogenesis. It was also found that KYZ could repair the vascular damage induced by PTK787 and promote the growth of subintestinal vessels in normal zebrafish. The result indicated that KYZ's angiogenic ability is better than the precursor compound caffeic acid (CA). In HUVECs, KYZ could promote cell proliferation, migration, and tube formation. A further mechanistic study suggested that the KYZ could induce the release of VEGF factor in HUVECs, up-regulate the expression of VEGFR2, and activate the AKT and ERK signaling pathways. Conclusions: These data show that KYZ may promote angiogenesis through VEGF, PI3K/AKT, and MEK/ERK signaling pathways, suggesting that KYZ exhibited great potential in the treatment of ischemic cardio-cerebrovascular diseases.